2013
DOI: 10.3408/jafst.18.79
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Genome Profiling Method for the Identification of Saliva and Sweat Samples

Abstract: The identiˆcation of body ‰uids at crime scenes provides critical evidence that can be used to prove the occurrence of a crime. In this study, the genome proˆling (GP) method was utilized to identify saliva and sweat. We randomly ampliˆed cDNA obtained through the RT PCR approach using RNA samples extracted from saliva and sweat with four diŠerent random primers, and performed temperature gradient gel electrophoresis between 15 65°C. The Sp 2 primer was the only primer which generated the species identiˆcat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Although mixed samples were not examined in this report, both genomes are expected to be randomly amplified, and it may be difficult to determine their species. In previous studies of virus detection using body fluids, we found species-specific spiddos [23, 24]. There may be specific spiddos in various species.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Although mixed samples were not examined in this report, both genomes are expected to be randomly amplified, and it may be difficult to determine their species. In previous studies of virus detection using body fluids, we found species-specific spiddos [23, 24]. There may be specific spiddos in various species.…”
Section: Discussionmentioning
confidence: 70%
“…It is possible to analyze information for the entire genome at a very low cost in a short period of time, without requiring any special knowledge or techniques. Using this GP method, we have identified human body fluid [22, 23] and viral species [24] and differentiated between humans and other mammalian species [25].…”
Section: Introductionmentioning
confidence: 99%
“…The GP method has been used to distinguish mammalian species [ 2 ] and human body fluid types [ 3 , 4 ] in the field of forensic medicine. However, it has not been used to distinguish species of virus.…”
Section: Introductionmentioning
confidence: 99%